The Didactics of the local history of Córdoba through the Archaeological Museum as an educational practice in the Primary Education Bachelor Degree (Praxis Educativa, 2021)
In these pages there are some of the results of a research carried out with the third-year students of the Primary Education Bachelor Degree of the subject of Didactics of Social Sciences, of the University of Córdoba, during the academic year 2019/2020. The aim is to know the perception of future teachers about the value of the Archaeological Museum as a didactic resource. In our opinion, it is a useful tool for understanding the closest environment and for learning the historical processes, establishing a dialogue between the particular and the general, the specific and the abstract, and local with global phenomena. Likewise, attention was paid to the teaching of heritage, an element that directly interrelates the environment and the life of our students. All this with the intention of optimizing the quality of the teaching-learning processes of the Social Sciences.
Keywords: Archeological Museum; Local history; heritage; primary education; Social Sciences